Hospitalized children's representations of their relationship with nurses and doctors. (September 2013) - Corsano, Paola; Majorano, Marinella; Vignola, Valentina; Cardinale, Elisa; Izzi, Giancarlo; Nuzzo, Maria Josè
This article reports an explorative study which aims to investigate hospitalized children's views of their relationships with nurses and doctors. Twenty-seven school-aged children and adolescents from 6 to 15 years old in the paediatric haematology and oncology ward of an Italian hospital participated in the study. Each participant was asked to draw him or herself with a doctor or nurse from the ward while they were doing something. The drawings were analysed using Pictorial Assessment of Interpersonal Relationships (PAIR) and a qualitative analysis. The results showed that the participants viewed their relationships with health professionals positively, in particular with the nurses. This relationship was perceived as close, intimate, cohesive and without conflict. In some cases it became an emotional bond. Finally, this relationship helped the patients to cope with painful and uncomfortable medical procedures, which gradually became familiar and accepted. The clinical implications of this study are discussed.